Actinobacillus pleuropneumoniae FliY and YdjN are involved in cysteine/cystine utilization, oxidative resistance, and biofilm formation but are not determinants of virulence - Zhao, Fan; Xu, Huan; Chen, Yubing; Xiao, Juan; Zhang, Miao; Li, Zhuo; Liu, Jinlin; Qi, Chao (Frontiers in Microbiology, 2023)
Actinobacillus pleuropneumoniae (A. pleuropneumoniae) is a member of Actinobacillus in family Pasteurellaceae. It is the causative agent of porcine pleuropneumonia, which has caused huge economic losses to pig industry over the world. Cysteine is a precursor of many important biomolecules and defense compounds in the cell. However, molecular mechanisms of cysteine transport in A. pleuropneumoniae are unclear. In this study, roles of potential cysteine/cystine transport proteins FliY and YdjN of A. pleuropneumoniae were investigated. Our results indicated that the growth of A. pleuropneumoniae was not affected after fliY or ydjN single gene deletion, but absence of both FliY and YdjN decreased the growth ability significantly, when cultured in the chemically defined medium (CDM) supplemented with cysteine or cystine as the only sulfur source. A. pleuropneumoniae double deletion mutant ΔfliYΔydjN showed increased sensitivity to oxidative stress. Besides, trans-complementation of YdjN into ΔfliYΔydjN and wild type leads to increased biofilm formation in CDM. However, the virulence of ΔfliYΔydjN was not attenuated in mice or pigs. These findings suggest that A. pleuropneumoniae FliY and YdjN are involved in the cysteine/cystine acquisition, oxidative tolerance, and biofilm formation, but not contribute to the pathogenicity of A. pleuropneumoniae.